Knowledge and Attitude of Antenatal Mother Regarding High-risk Pregnancy in a Tertiary Care Hospital in West-ern India - Aman Damor; Shreyash Mehta (Medsci Publications, 2021)
Introduction: A high-risk pregnancy is one of the major public health issues across the world including developing countries like India. Considering the importance of high-risk pregnancy, the present study was conducted to investigate the knowledge, attitudes, and practices of pregnant women at a tertiary care hospital in India. Methodology: A descriptive cross-sectional study with structured questionnaires to 100 registered pregnant women, aged between 18 and 45 years old was done. Results: All respondents have good knowledge, attitudes, and practices during pregnancy. The high-risk pregnancy status among respondents showed that there was no statistically significant differences to various socio-demographic variables (p >0.05). Conclusion: The participants have good knowledge, attitude and practices regarding high-risk pregnancy which indicate good penetration of IEC programme regarding the same. There was no difference in knowledge, attitude and practices among various socio-demographic groups.